Utilization of Management of Writing Scientific in the Learning Process in Higher Education - Moeins, Anoesyirwan; Sudaryono, Sudaryono; Khoirunisa, Alfiah (APTISI Transactions on Management (ATM), 2018)
In a scientific work, it is closely related to a writing management. Writing which is a writing activity is inseparable in the learning process. Writing can also be used as a management communication tool in conveying information. There are 4 (four) written communication elements as media tools. But recently a new paradigm has begun to develop that a management of scientific work does not have to be based on scientific research, but also a study of a problem that is analyzed professionally by experts. With the method of description using 5 (five) principles in the management of scientific writing to solve problems. So writing management is needed in compiling scientific papers in order to create good work by following the development of the industrial era 4.0. Thus, the task of intellectuals and intellectuals is not only able to read, but also must be able to manage writing about scientific writings and master the procedures for preparing scientific works. Utilization of Management of Writing Scientific Writing in the Learning Process in Higher Education. Keywords: management of scientific work, management of writing, scientific work.